Interface Design Principles For Malaysian Interactive Science Courseware - Kamaruddin, Norfadilah; Dolah, Jasni (2016)
In today’s Malaysian educational setting, most of the interactive courseware has been used as a new way to fully support the teaching and learning activity. Within these practices, the uptakes of interactive courseware in classroom were increased. Therefore, there are ongoing debates concerning the effectiveness used of the interactive courseware in classroom. Part of the arguments’ that had been acknowledged is deals with the quality of the interface design performance within the interactive courseware. Towards the issues concern, this paper discusses the 5 establish principles of interface design and its practical applications on the existing Malaysian interactive science courseware designed for the Smart School. The data describes in this paper is a part of the result from main research study undertaken on the development of a new doable set of interface design principles that is currently being completed. The new doable set of interface design principles moreover presuming will help the interface designers’ and the courseware developers in future development and improving the possibility of learning experiences